(untitled) (London Journal of Medical and Health Research, 2024)
From 2017 to 2023 a Self/Learning Sexual Education Online Course, (CESOLAA), is evaluated on 5 population groups. 3 courses were Closed to: 7 Pre- graduate health-student carriers, Summer post graduate courses and Teachers Assistant from 17 schools and other 2 MOOC Open type courses for Teachers and Assistant´s Educator and other course for General Public over 10 years old. Anonymous exploration is applied on Objectives Achievements and Quality Development of each Course, using previous proved evaluation instrument. The Closed Courses reached 89,1% (1.883/2.114) of approval and the Open Course reached 6,1% (251/4.089). The Objectives Achievements was classified as Good and Excellent in 95,2% for the Closed Courses and 91,8% for the Open Course. The Quality Development as Good and Excellent was classified in 96,6% and 93,1% for the 3 Closed Courses and 2 Open Courses, respectively. The big difference in these experiences, has been the significant lower proportion of participation in the Open course.